2020
DOI: 10.1016/j.ijpara.2020.03.015
|View full text |Cite
|
Sign up to set email alerts
|

The cellular and molecular origins of extracellular vesicles released by the helminth pathogen, Fasciola hepatica

Abstract: Parasitic helminths secrete extracellular vesicles (EVs) which have potent immunomodulatory effects. Whilst the cargo of EVs has been characterised for many species, we know little about the mechanisms that govern their biogenesis and release. Using antibodies raised against a panel of Fasciola hepatica EV (FhEV) marker proteins, we have identified multiple sites of EV production in the parasite. Discrete immunofluorescence patterns were observed within the gastrodermal cells and tegumental syncytium for diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…Key secretory proteins involved in immune modulation, host interaction and parasite survival have been identified as part of the ESP as free proteins or as components of EVs for a number of helminths. Annexins, actins, cathepsin proteases, heat shock proteins (HSPs), helminth defense molecules (HDMs), glutathione transferases (GSTs), and fatty-acid binding proteins (FABP) are among a number of such proteins that have been identified from Fasciola hepatica [ 27 , 30 , 45 , 46 , 47 , 48 ], Calicophoron daubneyi (Rumen Fluke) [ 21 , 49 ], Schistosoma japonicum [ 50 ], and Schistosoma mansoni [ 51 ] representing well characterised platyhelminths. Thus, in depth characterisation of helminth secretomes has the potential to uncover host parasite interaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Key secretory proteins involved in immune modulation, host interaction and parasite survival have been identified as part of the ESP as free proteins or as components of EVs for a number of helminths. Annexins, actins, cathepsin proteases, heat shock proteins (HSPs), helminth defense molecules (HDMs), glutathione transferases (GSTs), and fatty-acid binding proteins (FABP) are among a number of such proteins that have been identified from Fasciola hepatica [ 27 , 30 , 45 , 46 , 47 , 48 ], Calicophoron daubneyi (Rumen Fluke) [ 21 , 49 ], Schistosoma japonicum [ 50 ], and Schistosoma mansoni [ 51 ] representing well characterised platyhelminths. Thus, in depth characterisation of helminth secretomes has the potential to uncover host parasite interaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, inhibiting EV release from helminths would conceivably prevent delivery of miRNAs (and other bioactive molecules) to host immune cells. Recently, (Bennett et al, 2020) showed that a chemical inhibitor of EV biogenesis blocked the secretion of EVs from F. hepatica in vitro as initial proof-of-concept for such an approach. One of the major foci for parasite derived miRNAs has been their potential use as diagnostic biomarkers (Mu et al, 2021) We have identified at least 28 EV-derived secreted miRNAs from adult parasites, which could potentially represent PCR detectable indicators of mature fluke infections.…”
Section: Discussionmentioning
confidence: 99%
“…Again, platyhelminths show differences as EV release is seen directly from their tegument, a syncytium covering their bodies used for both protection and absorption of nutrients, which in nematodes is replaced by a collagenous extracellular cuticle. In the liver fluke F. hepatica , further evidence suggests that in addition to exosomes shed from the tegument (as indicated by their size and the presence of MVBs), most EVs are released through the gut and then oral sucker, with additional output from the protonephridial system through the parasite’s excretory pore ( Bennett et al, 2020a ).…”
Section: Helminth Extracellular Vesiclesmentioning
confidence: 99%
“…This correlates to differences in cellular origins of the EV sub-populations; with the larger 15k EVs released from gastrodermal cells lining the gut and 120k EVs seen beneath the gastrodermis, seemingly within the liver fluke excretory system ( De La Torre-Escudero et al, 2019 ). Physically ligating both the oral sucker and excretory pore of F. hepatica blocked the release of the 120k EVs but not the 15k population ( Bennett et al, 2020a ). A large amount of morphological variability is also seen in EVs from F. hepatica produced throughout the parasites lifecycle, from eggs, juveniles and adults ( Sánchez-López et al, 2020 ).…”
Section: Not All Evs Are Equalmentioning
confidence: 99%
See 1 more Smart Citation